دور تسيير الكفاءات في تحسين الاداء التنظيمي في المؤسسة - سميرة فرج; الزهرة قادري; عيدة رحاب بكوش; فدوى زلاسي (جامعة الوادي university of eloued, 2024)
" هدفت الدراسة إلى إبراز دور تسيير الكفاءات في تحسين الأداء التنظيمي في المؤسسة، وقد أجريت هذه الدراسة في جامعة الشهيد حمه لخضر بالوادي، و تم استخدام الاستبيان كأداة لجمع المعطيات، حيث تم توزيعها على عينة متكونة من 107 إداري، واسترجعت منها 104 استمارة، ولتحليل البيانات واختبار فرضيات الدراسة تم استخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS ، وبناء على تحليل النتائج توصلت الدراسة إلى أن تسيير الكفاءات هدفها تحسين الأداء التنظيمي داخل المؤسسة. " "Summary: The study aimed to highlight the role of competency management in improving organizational performance in the organization. This study was conducted at the University of Martyr Hama Lakhdar in El Oued. The questionnaire was used as a tool for collecting data. It was distributed to a sample of 107 administrators, from which 104 questionnaires were retrieved. To analyze the data and test the study hypotheses, the Statistical Package for the Social Sciences (SPSS) program was used, and Upon analyzing the results, the study concluded that competency management aims to improve organizational performance within the organization. "
Keywords: تسيير الكفاءات، الأداء التنظيمي، جامعة الشهيد حمه لخضر بالوادي; competency management; organizational performance; Shahid Hama Lakhdar University in El